A influência do constitucionalismo contemporâneo nas decisões dos tribunais nacionais e supranacionais: o diálogo entre as cortes - Ramos , Daniel Gomes de Souza (2018)
This work focuses on the influence of contemporary constitutionalism on the decisions of national and supranational courts, emphasizing the reasoning among the judges of these courts with the purpose of making human rights an universal panorama and bringing greater rationality to their defendants. It analyzes the evolution of constitutionalism, the main elements and behaviors of constitutional justice, as well as the theoretical instruments that examine the new methodology of constitutional law in the light of the present time. Besides, it brings practical cases arising from the Brazilian Supreme Court and from foreign courts for the protection of human rights.